Comparative Analysis of Biochemical Markers in Cardiovascular Disease Risk Assessment among Urban and Rural Populations in Pakistan - Iqra Hannan, Haseeb Ahmed Khan, Mohsin Shafi, Aaisha Qadir, Syedda Amina Rizvi, Salma Kadir, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Cardiovascular diseases (CVDs) are the most common cause of death worldwide and these diseases are quickly rising in prevalence in developing countries due to urbanization and changes in lifestyle. This study aimed to compare the role of biochemical markers in assessing of CVD risk factors in urban and rural populations of Pakistan. Study design: This study is a cross-sectional study of 120 subjects; 30–65 years of age and equally distributed in the urban (n = 60) and rural (n = 60) areas. Structured questionnaires were used to collect demographic data and lifestyle information. Total cholesterol (TC), low density lipoprotein (LDL), high density lipoprotein (HDL), triglycerides (TG), high sensitivity C reactive protein (hs-CRP), fasting blood glucose (FBG) were measured in their blood samples that were obtained after overnight fasting, using standard enzymatic methods. Body mass index (BMI) and waist to hip ratio (WHR) were also noted. Differences between the two groups were assessed by independent samples t tests and by multivariate analyses. Results: TC, LDL, TG and hs-CRP were significantly higher while HDL was significantly lower in urban residents compared to their rural counterparts (all p < 0.01). In addition, urban participants had a higher BMI and WHR (p < 0.005) suggesting increased obesity risk. However, FBG levels were higher in urban subjects; the difference was not statistically significant. Conclusion: The study shows that urban populations in Pakistan have a more adverse biochemical profile and therefore at greater risk of CVD. This underscores the need for targeted public health interventions and preventive strategies that target urban environments. Keywords: Cardiovascular disease, biochemical markers, urbanization, rural health, lipid profile, hs-CRP, obesity, Pakistan.